Analysis of Road Embankment Improvement on Soft Soil Using Foamed Mortar Lightweight Embankment - Permana Putuarga, Alfiady Reza; Mochtar, Indrasurya B.; Mandarsyah, Dedy (Journal of Infrastructure & Facility Asset Management, 2024)
The Calang - Simpang Peut road section, linking Banda Aceh and Meulaboh in Aceh Province, faces severe damage, including longitudinal cracks, pavement settlement, and embankment deformation. Soil testing reveals a soft soil layer beneath the embankment. Alternative treatments that can be used to deal with stability and settlement problems on soft soils are to use foamed mortar lightweight materials. The research evaluates the untreated embankment and the use of foam mortar with varying thickness and slope. Stability, settlement, and uplift pressure are analyzed. The analysis showed that the untreated embankment had a factor of safety of 1.090, close to critical. Improvement of the embankment using foam mortar can increase the factor of safety and reduce settlement as the thickness of the foam mortar increases. The thickness of foam mortar that meets the requirements for the existing slope embankment is 1.50 meters thick or more and for the vertical slope embankment is 2.00 meters thick or more.